Why Are We Unfaithful? Initial Application of a Scale to Estimate the Reasons Why Men and Women Are Unfaithful - Fernandez-Tapia, A; Figueroa-Valdebenito, O; Jara-Duran, C (AIDEP, 2018)
This research aimed at generating a scale about the reasons for infidelity in men and women, from an evolutionary perspective. The Reasons for Infidelity Scale (RPI) was administered to 311 undergraduate and graduate students from Universidad de Santiago de Chile. The results exhibited acceptable internal consistency and moderate temporal stability 40 days after the initial application. An exploratory factor analysis resulted in two dimensions to account for the 12 items in the final scale: relationship dissatisfaction and sexuality. A positive association of the dimension of sexuality of the RPI and sociosexuality, as well as a negative correlation of the dimension of sexuality of the RPI and relationship quality evidenced the convergent validity of the scale. Sex differences were observed in the dimension of sexuality. These results are consistent with the predictions in which the study is based.